(untitled) (Research, Society and Development, 2022)
Objective: to analyze the experiences and difficulties of pregnant adolescents regarding the use of contraceptive methods. Methodology: this is a descriptive and exploratory study, of a quantitative-qualitative nature, carried out with adolescents who undergo prenatal care at a health unit in a municipality in the interior of Paraná. Fifteen adolescents, aged between 13 and 17 years old, participated in the research. A data collection instrument was applied in the period of April 2022. In addition to age, the following variables were analyzed: race/color, family income, marital status, education, number of pregnancies, contraceptive use and knowledge, pregnancy planning and complications in pregnancy. Results: 93.9% of the adolescents were between 14 and 17 years old, all of them knew about contraceptives, the male condom was the most used method and 73% did not have a planned pregnancy. Conclusion: teenage pregnancy is still a very present reality within society, despite all the alternatives of information and access to available methods.